1991
DOI: 10.1046/j.1537-2995.1991.31992094672.x
|View full text |Cite
|
Sign up to set email alerts
|

A flow cytometric method for determination of white cell subpopulations in filtered red cells

Abstract: A flow cytometric method for the detection of low amounts of lymphocytes, monocytes, and granulocytes in filtered red cells (RBCs) was evaluated. In this procedure, the RBCs in the samples were lysed by ammonium chloride treatment and the white cells (WBCs) were detected by flow cytometry according to their specific light-scattering properties. The identity of the WBC subpopulations was confirmed by immunofluorescence with monoclonal antibodies specific for each cell type. Flow cytometric determination of WBCs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

1992
1992
2000
2000

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…However, below 20 fluorescence events, we observed a have shown that leucocyte-depleting platelet filters differ ing in their overall efficacy also differed in their relative efficacy in absorbing different lymphocyte subsets, so that the less-efficient filter removed more dendritic cells, thought to be of central importance in inducing alloimmu nization [27]. Al et al [22] characterised the different leucocyte classes on the basis of light scatter. Although they confirmed the identity of the cells using fluoresceinlabelled monoclonal antibodies, we feel that immunophenotyping as used by us and others [20,21] is a more reliable method, as changes to light-scattering properties, e.g.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, below 20 fluorescence events, we observed a have shown that leucocyte-depleting platelet filters differ ing in their overall efficacy also differed in their relative efficacy in absorbing different lymphocyte subsets, so that the less-efficient filter removed more dendritic cells, thought to be of central importance in inducing alloimmu nization [27]. Al et al [22] characterised the different leucocyte classes on the basis of light scatter. Although they confirmed the identity of the cells using fluoresceinlabelled monoclonal antibodies, we feel that immunophenotyping as used by us and others [20,21] is a more reliable method, as changes to light-scattering properties, e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies [20][21][22] have described the use of flow cytometry for this purpose. Freedman et al [20] The change in transfusion policy described in Methods is summarised in figure 2.…”
Section: Effect Of Rcc Processing On Amount and Type Of Residual Leucmentioning
confidence: 99%
See 1 more Smart Citation
“…Leucocyte counting was achieved by flow cytometry on a Becton Dickinson FACSort using the Becton Dickinson LeucoCOUNT kit, and in some cases by visual microscopy using a Nageotte chamber. The method of flow cytometric evaluation of residual leucocytes involved staining with propridium iodide (Al et al , 1991; Deneys et al , 1994; Dzik, 1997). This approach was validated for sensitivity and linearity by spiking of double‐filtered units with fresh whole blood, and allows enumeration to a level of 2 × 10 5 per unit (data not shown).…”
Section: Methodsmentioning
confidence: 99%
“…Counting leukocytes in RCC becomes more difficult as their number decreases. Although counting methods with the flow cytometer [22] or a radioimmunoassay [23] can be applied, we showed in this study that dilution of the sam ple in Turk's solution and the use of a Bürker hemocytometer suffice for routine checks. The use of the Fuchs-Rosenthal hemocytometer or fluorescent microscopy did not give clearer results.…”
Section: Leukocyte Countingmentioning
confidence: 86%